Solar Ultraviolet Radiation and Vitamin D Deficiency on Epstein-Barr Virus Reactivation: Observational and Genetic Evidence From a Nasopharyngeal Carcinoma-Endemic Population. (12th September 2020) - Mai, Zhi-Ming; Lin, Jia-Huang; Ngan, Roger Kai-Cheong; Kwong, Dora Lai-Wan; Ng, Wai-Tong; Ng, Alice Wan-Ying; Ip, Kai-Ming; Chan, Yap-Hang; Lee, Anne Wing-Mui; Ho, Sai-Yin; Lung, Maria Li; Lam, Tai-Hing
Abstract: Background: We investigated the relationship of Epstein-Barr virus viral capsid antigen (EBV VCA-IgA) serostatus with ambient and personal ultraviolet radiation (UVR) and vitamin D exposure. Methods: Using data from a multicenter case-control study, we included 1026 controls subjects in 2014–2017 in Hong Kong, China. Odds ratios (ORs) and 95% confidence intervals (CIs) of the association between UVR exposure and EBV VCA-IgA (seropositivity vs seronegativity) were calculated using unconditional logistic regression models adjusted for potential confounders. Results: We observed a large increase in seropositivity of EBV VCA-IgA in association with duration of sunlight exposures at both 10 years before recruitment and age 19–30 years (adjusted OR = 3.59, 95% CI = 1.46–8.77; and adjusted OR = 2.44, 95% CI = 1.04–5.73 for ≥8 vs <2 hours/day; P for trend = .005 and .048, respectively). However, no association of EBV VCA-IgA serostatus with other indicators of UVR exposure was found. In addition, both circulating 25-hydroxyvitamin D (25OHD) and genetic predicted 25OHD were not associated with EBV VCA-IgA serostatus. Conclusions: Our results suggest that personal UVR exposure may be associated with higher risk of EBV reactivation, but we did not find clear evidence of vitamin D exposure (observational or genetic), a molecular mediator of UVR exposure. Further prospective studies in other populations are needed to confirm this finding and to explore the underlying biological mechanisms. Information on photosensitizing agents, and serological markers of EBV, and biomarkers related to systemic immunity and inflammation should be collected and are also highly relevant in future studies.